Urban Tree Selection for Diversity - Deborah R. Hilbert; Andrew K. Koeser; Robert J. Northrop (EDIS)
Urban tree diversity is important when attempting to create a healthy, beneficial, and resilient urban forest. Having a variety of trees can increase the aesthetic value for residents and create habitats for plants and animals. Some common street trees currently in the landscape are not site-appropriate and create infrastructure damage. By planting different types of trees in these locations, maintenance costs and infrastructure damage can be reduced and tree longevity increased. This new 4-page fact sheet is intended to provide urban foresters, arborists, landscape designers, and others in charge of tree planting with a process for introducing new species into the urban environment. Written by Deborah R. Hilbert, Andrew K. Koeser, and Robert J. Northrop, and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep589